Comparative study on inorganic Cl removal of municipal solid waste fly ash using different types and concentrations of organic acids. (December 2020) - Wang, Xiaona; Wang, Menglu; Zou, Dezhi; Wu, Chuanfu; Li, Teng; Gao, Ming; Liu, Shu; Wang, Qunhui; Shimaoka, Takayuki
Abstract: In this study, different organic acids—such as citric, acetic, lactic, propionic, and butyric acid—were evaluated to ascertain the optimum leaching solvent for dechlorinating fly ash. Results suggest that the acid type, concentration, and interactions between both parameters contributed significantly to the variations in the efficiency of fly ash dechlorination. Simple main-effect analysis suggested that a higher acid concentration yields better dechlorination efficiency. However, improvements in dechlorination efficiency did not necessarily yield a low chlorine content leaching residue because in a specific acid concentration region, the increased acid concentration may also accelerate the mass reduction rate of the leaching residue. Experimental results also demonstrate that citric and acetic acid yield the highest dechlorination efficiency, followed by propionic and butyric acid. The least dechlorination efficiency of lactic acid could be attributed to the formation of precipitate (i.e. calcium lactate) which might cover the chlorides and reduce the contact area of intimal chlorides with the leaching solvent. Therefore, a specific concentration of organic matter fermentation broth rich in citric and acetic radicals may present itself as an ideal water substitute for fly ash dechlorination. Graphical abstract: Image 1 Highlights: Dechlorination of fly ash by different organic acids was investigated. Acid type, concentration, and interactions contributed significantly to Cl removal. Little relationship between dechlorination efficiency and chlorine content residue. Citric and acetic acid fermentation broth were ideal solvents for dechlorination.